Comparison of Small and Medium Sized Enterprises in Europe. - Karmel, Solomon M. (Routledge studies in business organization and networks., 2002)
Developed from a study commissioned by the European Capital Markets Institute, this book examines the impact of private equity and capital markets on the development of small and medium sized enterprises in the USA and European Union.